FAKTOR PENYEBAB KERACUNAN AKUT PENGGUNAAN PESTISIDA PADA PETANI DI DESA PONORAGAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Dina Lusiana S (Universitas Widya Gama Mahakam Samarinda, 2016)
Acute pesticide poisoning resulting from the use of pesticides that enter the body. Ponoragan village, is an agricultural area so that the majority of the population worked as farmers who have suffered acute poisoning risks resulting from the use of pesticides. Cholinesterase examination results by the District Health Office Kutai is obtained from 223 farmers who checked there are 100 farmers who suffered acute poisoning due to exposure to pesticides. Improper use of pesticides will cause acute poisoning among farmers. The purpose of this study was to determine the relationship PPE use, work of service, and duration of exposure and acute poisoning pesticide on farmers in the Ponoragan. This type of research is analytic survey with cross sectional approach. Collecting data using by a questionnaire with a sample of 69 people. The results showed that there was no relationship between duration of exposure (p = 0.290) with acute pesticide poisoning. There was a relationship between of work of service (p = 0.025), the use of PPE (p = 0.052) and acute pesticide poisoning.